The Influence of Service Quality on Employee Performance in the PSMA Sector at the West Java Provincial Education Office. - Karen Laura; Janah Sojanah; Rasto Rasto; Yosep Hernawan; Mardiman Mardiman (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study was motivated by the inconsistency in employees’ work target achievement within the PSMA Division of the West Java Provincial Education Office, which is presumed to be associated with the suboptimal implementation of both internal and external service standards. The study aims to empirically examine the extent to which perceived service quality influences employee performance in the organization. An explanatory quantitative approach was employed, involving all 41 employees through a census sampling technique. Data were collected using a five-point Likert scale questionnaire that had demonstrated satisfactory validity and reliability. The data were analyzed using descriptive statistics and simple linear regression with the assistance of SPSS software. The findings reveal that service quality has a positive and significant effect on employee performance (β = 0.330, p = 0.020), with a coefficient of determination of 55.3%. Descriptive analysis further indicates that service quality is perceived at a very high level (mean = 4.31), while employee performance is categorized as high (mean = 4.17). These findings suggest that improving and standardizing service quality can serve as an important mechanism for enhancing employee productivity and organizational performance within public sector institutions.